Kajian Visualisasi Iklan Layanan Masyarakat “Sumpah Pemuda” - Tunjung Riyadi (Humaniora, 2011)
Watching television advertising means accepting the message and understand the meaning of the message from those impressions. With a fairly short duration, the audience is faced with the question of understanding various aspects. The first aspect is the accessibility to the senses of the eye and ear and continues to the senses understanding of meaning and sense and consideration. Semiotics is one approach to understanding television advertising where the ad itself as part of the marker system information. From the nature of information just to process an attempt "to seduce" the audience in this case is the prospect of a commercial nature. Message becomes differently if it is not commercial. There is no end goal of selling products, but simply pass on the positive message. This is what will be studied from a television ad social services with the youth oath-theme. The review focused on the aspects of ease of understanding the visual language of scene after watching this public service advertisements.